Study on heat input for superalloy welding by using FEA simulation and experimental verification / Gege Nurfaizee Fadzil. - Fadzil, Gege Nurfaizee (2009)
The purpose of this study is to find out optimum heat source for IN625 nickel based super alloy by using experimental and finite element analysis. The investigation on heat source was use in the welding process in order to seek the relationship between mechanical characteristic and macrostructure. It also employed in order to find out the optimum heat source on butt join and had included simulation (SYSWELD). Information in IN625 coupons parameter such as variable current, voltage and traveling speed while welding have been taken and was applied in SYSWELD. The distortion effects from welding works are then being measure by using CMM. The hardness values are taken by portable Hardness Vickers equipment. The macro graph from experimental measured to develop heat source fitting for SYSWELD application. It is hope that by using simulation software the time taken to predicting outcome of super alloys welding can be shortened hence avoiding trial and error method which currently being employed.